2016
DOI: 10.1159/000448706
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of Chronic Pain Assessment after Inguinal Hernia Repair: A Critical Review of the Literature

Abstract: Background: Chronic postoperative inguinal pain (CPIP) is the most common long-term complication of inguinal hernia repair. As such procedures are routinely performed, CPIP can be considered a significant burden to global health care. Therefore, adequate preventative measures relevant to surgical practice are investigated. However, as no gold standard research approach is currently available, study and outcome measures differ between studies. The current review aims to provide a qualitative analysis of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 93 publications
(255 reference statements)
0
19
0
Order By: Relevance
“…At the same time, synthetic mesh (GoreBio-A; W. L. Gore, Flagstaff, AZ, USA), with resorption time similar to the biological mesh mentioned above, shows higher rates of recurrence in patients with IH treated with an open surgical technique. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, synthetic mesh (GoreBio-A; W. L. Gore, Flagstaff, AZ, USA), with resorption time similar to the biological mesh mentioned above, shows higher rates of recurrence in patients with IH treated with an open surgical technique. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Pain reports at 3 months may represent more the frequency of natural short-term postoperative pain, as other authors have suggested. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…These PROMs consider general characteristics and not symptoms specific to only one disease or condition (10, 11, 21). Numerous generic PROMs exist, and two of the most commonly used are the Short-Form 36 Health Survey and the visual analog scale ( Table 1) (4,42). A generic PROM can be considered more of a global health measure than any condition-specific PROM, and it is a more comprehensive insight into the current health status of the patient (43).…”
Section: Generic Promsmentioning
confidence: 99%
“…In inguinal hernia research, the use of generic PROMs greatly exceeds the use of condition-specific PROMs (4,42). This is unfortunate since generic PROMs generally lack content validity in the context of hernia repair.…”
Section: Generic Promsmentioning
confidence: 99%
“…There is an enormous variation of the rate of pain after hernioplasty in the literature (20-45%) [40,41]. This variation could be explained by the fact that many aspects are not uniform in those pain studies: method and timetabling for pain measurement, definition of chronic pain and its distinction from discomfort, selection criteria of the patients, assessment or not of the pre-operative pain among others [40]. All this impedes a comparison of the risk of CPP with similar trials.…”
Section: Chronic Post-operative Pain and Degradable Meshesmentioning
confidence: 99%